The Intensification of the Cultivation Technologies and the Ecological Quality of Black Currants (R. nignirum L.) Fruit - Kuyan, Vladimir G.; Ovezmyradova, Olga B.; Yevtushok, Ivan M. (Journal of the Belarusian State University. Ecology, 2019)
The paper gives a brief analysis of black currants (R. nignirum L.) culture in variable climatic and soil conditions within the period of its industrial cultivation. In particular, the paper draws attention to the intensification processes of fruit growing, the expansion and the considerable improvement of a sort composition, the plantation consideration, the intensification of supplying the elements of mineral feeding by rising the rates of organic and especially mineral fertilizers, the cardinal improvement of the plants chemical protection, the improvement of the bushes shaping and trimming which will provide the 10–15 t/ha and more yields increase. The content of Pb in fruit has 5–25 % excess in terms of MPC, Cd content is 2–4 times as big in the by-highway areas. The specific activity indexes of 137Cs and 90Sr in the absolute evacuation zones do not exceed an accepted level. Fruit are ranked as ecologically safe.
Keywords: black currant; varieties; technologies; intensification; heavy metals; crop yield; zones located in proximity to the highways; radionuclides; ecological quality